A metaphor is haunting the world (Papeles, 2018)
The article examines the role of metaphors regarding the development and the teaching of science in general and of economic science in particular. Examples from physics and biology are discussed and the “invisible hand” metaphor is briefly analyzed in the context of Adam Smith political economy and Milton Friedman positive economy.
Keywords: metaphor; pedagogy; economic science